The metabolic role of prolactin: systematic review, meta-analysis and preclinical considerations. Issue 6 (2nd November 2022) - Corona, Giovanni; Rastrelli, Giulia; Comeglio, Paolo; Guaraldi, Federica; Mazzatenta, Diego; Sforza, Alessandra; Vignozzi, Linda; Maggi, Mario
ABSTRACT: Introduction: Hyperprolactinemia has been proven to induce hypogonadism and metabolic derangements in both genders, while the consequences of prolactin (PRL) deficiency have been poorly investigated. Areas covered: To systematically review and analyze data from clinical studies focusing on the metabolic consequences of abnormally high prolactin levels (HPRL) and low prolactin levels (LPRL). In addition, data from preclinical studies about underlying pathophysiological mechanisms were summarized and discussed. Expert opinion: PRL contributes to providing the correct amount of energy to support the mother and the fetus/offspring during pregnancy and lactation, but it also has a homeostatic role. Pathological PRL elevation beyond these physiological conditions, but also its reduction, impairs metabolism and body composition in both genders, increasing the risk of diabetes and cardiovascular events. Hence, hypoprolactinemia should be avoided as much as possible during treatment with dopamine agonists for prolactinomas. Patients with hypoprolactinemia, because of endogenous or iatrogenic conditions, deserve, as those with hyperprolactinemia, careful metabolic assessment.